2010
DOI: 10.1108/ijotb-13-04-2010-b005
|View full text |Cite
|
Sign up to set email alerts
|

Technology adoption and organizational culture in public organizations

Abstract: Organization culture and technology adoption are two of the most critical issues facing organizations in a global society. Increasingly, organizations operate in uncertain, networked, decentralized environments, where adoption and use of information technology has become central to fulfilling organizational missions. To examine the influence of organization culture on individual willingness to adopt technology, this work began by examining theories of behavioral intent, technology adoption, and organization cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Bhattacherjee (2006) identified a positive effect of informational messages with source credibility on potential users' attitude toward IT. Hence, we hypothesize: H1: Information is positively related to attitude towards using IT An individual's general willingness to adopt technology is positively related with the communication flow in public organizations (Melitski, Gavin, & Gavin, 2010). Räckers et al (2013) found that communication has a significant influence on behavioural intention to use IT.…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…Bhattacherjee (2006) identified a positive effect of informational messages with source credibility on potential users' attitude toward IT. Hence, we hypothesize: H1: Information is positively related to attitude towards using IT An individual's general willingness to adopt technology is positively related with the communication flow in public organizations (Melitski, Gavin, & Gavin, 2010). Räckers et al (2013) found that communication has a significant influence on behavioural intention to use IT.…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…They are either individuals or companies who use the value created by the system. Melitski et al (2010) suggest that public organizations are acting in ecosystems as well. However this study does not regocnize governments as true parts of the ecosystem, yet they are still very much involved as they set the legislative frameworks in which the ecosystem must operate and might grant some financial support for innovations (Clarysse et al, 2014).…”
Section: Business Ecosystemsmentioning
confidence: 99%
“…J. Melitski, D. Gavin & J. Gavin (2010) state that culture is the black box of which an organisation will be recognised, assessed, and evaluated on (Melitski, Gavin & Gavin, 2010).…”
Section: Resultsmentioning
confidence: 99%